Mesoporous CoFe2O4 nanowires: Nanocasting synthesis, magnetic separation and enhanced catalytic degradation for ciprofloxacin. (September 2019) - Chen, H.D.; Xu, J.K.; Wei, J.Q.; Wang, P.F.; Han, Y.B.; Xu, J.C.; Hong, B.; Jin, H.X.; Jin, D.F.; Peng, X.L.; Li, J.; Yang, Y.T.; et al.
Abstract: Mesoporous CoFe2 O4 nanowires (NWs) were prepared with ordered mesoporous SBA-15 silica, and then were used to activate peroxymonosulfate (PMS) to degrade ciprofloxacin (CIP). All results showed that mesoporous CoFe2 O4 NWs efficiently activated PMS and greatly improved the degradation of CIP in aqueous solution. The influence of PMS and CoFe2 O4 on the CIP removal was taken into accounted, which indicated that the dominant sulfate radicals for the CIP degradation. Mesoporous-structure of CoFe2 O4 NWs could absorb CIP and PMS in high concentration near CoFe2 O4 NWs and promoted this degradation. The 100 ml CIP (20 mg/L) could be completely removal in the optimum conditions with 2 mM PMS and 0.3 g/L S-130, and the CIP removal presented the excellent recyclability with the CIP degradation as high as about 93% after four consecutive cycles. Owing to the high efficiency, excellent magnetic respond and good reusability, mesoporous-structured CoFe2 O4 NWs could be regarded as the promising heterogeneous catalysts for PMS to degrade CIP. Graphical abstract: Image 1 Highlights: Mesoporous CoFe2 O4 NWs greatly activated PMS to degrade CIP. Mesoporous-structure absorbed CIP in high concentration and promoted reaction. CoFe2 O4 presented the good repeatable catalysis and could be recycled. CoFe2 O4 NWs were easily separated by magnetic separation technique. The sulfate radicals were the dominated active radicals to degrade CIP.